A sumoylation program is essential for maintaining the mitotic fidelity in proliferating mantle cell lymphoma cells - Walter Hanel; Pushpa Lata; Youssef Youssef; Ha Tran; Liudmyla Tsyba; Lalit Sehgal; Bradley W. Blaser; Dennis Huszar; JoBeth Helmig-Mason; Liwen Zhang; Morgan S. Schrock; Matthew K. Summers; et al. (Experimental Hematology & Oncology, 2022)
Abstract Background Mantle cell lymphoma (MCL) is a rare, highly heterogeneous type of B-cell non-Hodgkin’s lymphoma. The sumoylation pathway is known to be upregulated in many cancers including lymphoid malignancies. However, little is known about its oncogenic role in MCL. Methods Levels of sumoylation enzymes and sumoylated proteins were quantified in MCL cell lines and primary MCL patient samples by scRNA sequencing and immunoblotting. The sumoylation enzyme SAE2 was genetically and pharmacologically targeted with shRNA and TAK-981 (subasumstat). The effects of SAE2 inhibition on MCL proliferation and cell cycle were evaluated using confocal microscopy, live-cell microscopy, and flow cytometry. Immunoprecipitation and orbitrap mass spectrometry were used to identify proteins targeted by sumoylation in MCL cells. Results MCL cells have significant upregulation of the sumoylation pathway at the level of the enzymes SAE1 and SAE2 which correlated with poor prognosis and induction of mitosis associated genes. Selective inhibition of SAE2 with TAK-981 results in significant MCL cell death in vitro and in vivo with mitotic dysregulation being an important mechanism of action. We uncovered a sumoylation program in mitotic MCL cells comprised of multiple pathways which could be directly targeted with TAK-981. Centromeric localization of topoisomerase 2A, a gene highly upregulated in SAE1 and SAE2 overexpressing MCL cells, was lost with TAK-981 treatment likely contributing to the mitotic dysregulation seen in MCL cells. Conclusions This study not only validates SAE2 as a therapeutic target in MCL but also opens the door to further mechanistic work to uncover how to best use desumoylation therapy to treat MCL and other lymphoid malignancies.